The Use of AR Technology to Overcome Online Shopping Phobia: A Systematic Literature Review - Shah Kazmi, Syed Sibtain Ali; Hassan, Muhammad; Khawaj, Shahid Ali; Falindah Padlee, Siti (International Journal of Interactive Mobile Technologies (iJIM), 2021)
With every year’s start being a new beginning and a source of happiness, reigniting hopes and optimism around the world, the happiness and enjoyment of the year 2020 faded away quite earlier. It was not long into the year 2020 that the notorious COVID-19 hit the world. Millions of people died of it and billions of people got affected by it either directly or indirectly. With its impact on everybody, it drastically affected the business world as well; individuals lost their jobs and companies lost their businesses. However, companies learned to respond to the pandemic by converting their businesses to the online business model and the customers also shifted to online shopping. With this compelling shift, the customers still had the phobia of online shopping and tried to abstain from it as much as possible. To respond to this, a systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was developed to offer a systematic and holistic literature review of the research regarding customer confidence in online shopping particularly by the use of Augmented Reality (AR) technology. The database of this review includes a set of 54 systemically selected state-of-the-art articles from Scopus database covering empirical and theory research conducted in different countries with different resource endowments. The results show that the use of AR technology can help customers in overcoming their shopping phobia and thus, it can be a source of enhanced online business for companies. Some possible opportunities for future research are also illustrated in this paper.